The prevalence of atopic diseases and the patterns of sensitization in adolescence. Issue 8 (5th October 2016) - Christiansen, Elisabeth Soegaard; Kjaer, Henrik Fomsgaard; Eller, Esben; Bindslev‐Jensen, Carsten; Høst, Arne; Mortz, Charlotte Gotthard; Halken, Susanne
Abstract: Background: Atopic diseases are among the most common chronic diseases in adolescents, and it is uncertain whether the prevalence of atopic diseases has reached a plateau or is still increasing. The use of the ISAAC (International Study of Asthma and Allergy in Childhood) questionnaire has provided comparable prevalence rates from many countries, whereas studies including clinical examinations and strict diagnostic criteria are scarce. We aimed to investigate the prevalence of atopic diseases, the pattern of sensitization, and comorbidities at 14 years in a prospective birth cohort. Methods: The children were examined eight times from birth to 14 years. Visits included questionnaire‐based interviews, clinical examination, skin prick test, and specific IgE. Results: Follow‐up rate at 14 years was 66.2%. The 12‐month prevalence of any atopic disease was high (40.3%) mostly due to a high prevalence of rhinoconjunctivitis (32.8%), whereas the prevalence of asthma was 12.9% and of atopic dermatitis 8.1%. In children with at least one atopic disease, 60% were sensitized, while only 16% of those without atopic diseases were sensitized. The frequency of sensitization depended on the phenotype. Among children with rhinoconjunctivitis only, rhinoconjunctivitis with concomitant asthma or atopic dermatitis or both 62.5%, 81.5%, 70%, and 100%, respectively, were sensitized, whereas it was 7.7% and 33.3% of children with only asthma or atopic dermatitis. Conclusion: The prevalence of rhinoconjunctivitis was high in adolescence. Children with rhinoconjunctivitis with and without comorbidities were frequently sensitized. Children with asthma without concomitant allergic rhinoconjunctivitis were rarely sensitized.